1981
DOI: 10.2190/e6y3-tpvm-mtu0-rcw3
|View full text |Cite
|
Sign up to set email alerts
|

The Family and Home Hemodialysis: Adolescents' Reactions to a Father on Home Dialysis

Abstract: Quality of life is the most controversial issue surrounding home hemodialysis. We examined how sixteen adolescents and their six families reacted to having a father on home hemodialysis, exploring the interplay between adolescent developmental conflicts and family stresses. Family members underwent role changes to adjust to alterations imposed by hemodialysis. Some adolescents helped relieve family stresses by taking an active role in dialysis. These eight adolescents developed greater self-esteem which enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…The study concluded that these children appeared to have what was necessary for a good life, although more information, particularly in relation to how other family members were feeling and specifically regarding parental condition and treatment, would further improve it. This is similar to the findings of Goldman et al . (1980–1981), and highlights the need for relevant information which is accessible to the child.…”
Section: Specific Needs Of Childrensupporting
confidence: 93%
See 4 more Smart Citations
“…The study concluded that these children appeared to have what was necessary for a good life, although more information, particularly in relation to how other family members were feeling and specifically regarding parental condition and treatment, would further improve it. This is similar to the findings of Goldman et al . (1980–1981), and highlights the need for relevant information which is accessible to the child.…”
Section: Specific Needs Of Childrensupporting
confidence: 93%
“…
Families were asked to participate in the study if the family included at least one son or daughter between the ages of twelve and twenty‐one years who was living at home (or who had lived at home within five years prior to the study) while a parent was on home dialysis. (Goldman et al . 1980–1981, p. 236)
…”
Section: Specific Needs Of Childrenmentioning
confidence: 99%
See 3 more Smart Citations